2010
DOI: 10.1111/j.1537-2995.2009.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

The aptamer ARC1779 blocks von Willebrand factor–dependent platelet function in patients with thrombotic thrombocytopenic purpura ex vivo

Abstract: ARC1779 potently and specifically inhibits VWF activity and VWF-dependent PLT function. ARC1779 may be a promising novel therapeutic for the treatment of TTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 38 publications
(41 reference statements)
4
40
0
Order By: Relevance
“…Today clinical trials are ongoing for two compounds targeting the protein partners of this complex (either VWF-A1 or GPIb␣) (7)(8)(9)(10)(11), and as anticipated, platelet function is dose-dependently inhibited, importantly without causing bleeding effects or interference with normal hemostasis. Recently, OS1, an 11-mer cysteine-constrained cyclic peptide, has been identified, and by targeting GPIb␣ it inhibits agonistinduced platelet aggregation by stabilizing the ␤-switch forming loop region in an alternative ␣-helical conformation (62,63).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Today clinical trials are ongoing for two compounds targeting the protein partners of this complex (either VWF-A1 or GPIb␣) (7)(8)(9)(10)(11), and as anticipated, platelet function is dose-dependently inhibited, importantly without causing bleeding effects or interference with normal hemostasis. Recently, OS1, an 11-mer cysteine-constrained cyclic peptide, has been identified, and by targeting GPIb␣ it inhibits agonistinduced platelet aggregation by stabilizing the ␤-switch forming loop region in an alternative ␣-helical conformation (62,63).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, initial studies showed that Fab fragments of anti-GPIb␣ monoclonal antibodies (mAbs) that block VWF binding inhibited thrombus formation in vivo without significant prolongation of the bleeding time in non-human primates (4 -6). For other inhibitors of the GPIb␣-VWF interaction, such as the VWF-A1 binding aptamer ARC1779 (7)(8)(9) and the humanized bivalent Nanobody ALX-0081 (10,11), the antithrombotic potential and safety in initial human clinical trials has been indicated.…”
mentioning
confidence: 99%
“…12 Dose response curves for ARC1779 indicate that the affinity of ARC1779 to the VWF A1 free domain is comparable between healthy volunteers, patients with TTP, or those with VWF disease. 12,13,25 This is an indicator that the capacity of ARC1779 is roughly comparable in subjects with normal, low or high multimer composition.…”
Section: Discussionmentioning
confidence: 99%
“…This high degree of specificity of ARC15105 is in good agreement with the high specificity of the predecessor ARC1779. 11,25 The investigated pegylated aptamer ARC15105 has been developed to provide a long-lasting inhibition of VWF after SC injection. Indeed, the formulation provided 98% bioavailability after SC injection, and the half-life is Ϸ65 hours.…”
Section: Discussionmentioning
confidence: 99%
“…78 It has been proposed that the balance between ADAMTS13 activity and VWF can be restored, even in the presence of ADAMTS13 autoantibodies, using N-acetylcysteine, which reduces the VWF intra-A1 and intersubunit disulfide bonds, thereby altering the mean size and platelet adhesive function of VWF multimers in vitro and in vivo 79 ( Figure 3B). Alternatively, acute episodes of TTP might be attenuated by pharmacologic inhibition of the interaction of platelet GPIb with the A1 domain of VWF using an anti-VWF aptamer (eg, ARC1779) 80,81 or nanobody (eg, ALX-0081) [82][83][84] (Figure 3C). A continuous infusion of ARC1779 suppressed VWF activity and led to a rise in platelet counts in patients with hereditary TTP.…”
Section: Ttp: Autoantigen Functionmentioning
confidence: 99%